(untitled) (Journal of Science and Technology, 2022)
This paper presents a comprehensive method to manage domestic waste and provides a detailed design of an alert sub-system, which is one of the blocks of the proposed waste management system. The waste management system entails various blocks on activities, from preparatory to implementation. The alert sub-system uses an ultrasonic sensor to monitor the level of waste in a bin and notifies a waste collection company when the bin is full and requires emptying, via short messaging service (SMS). It also allows the user to query the state of the bin at any time. The alert sub-system is simple to implement, inexpensive, uses less power, and will enable effec-tive and efficient waste collection. The implementation of the proposed waste management sys-tem should improve the collection and disposal of domestic waste.